2017
DOI: 10.1016/j.clinthera.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Systemic Corticosteroid Exposure: A Systematic Literature Review

Abstract: Although doses of long-term corticosteroids have fallen over the past several decades in response to AEs, dose reduction may not be a sufficient solution. Numerous AEs, some very costly, persist among long-term corticosteroid users, suggesting a need for further research to fill current data gaps, as well as a potential need for alternative treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
266
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(282 citation statements)
references
References 36 publications
4
266
1
11
Order By: Relevance
“…Like our meta-analysis, Farne et al also observed a modest improvement in quality of life and a small improvement in lung function in both mepolizumab- and reslizumab-treated patients. The clinical outcomes in our study were comparable to the outcomes investigated by Farne et al, except that we included OCS maintenance dose reduction and discontinuation as critical outcomes, because the risk of serious adverse events are substantial with such treatment regimen [36]. Importantly, the study by Farne et al, although largely including the same studies, does not provide an inter-drug comparison of efficacy and safety.…”
Section: Discussionsupporting
confidence: 52%
“…Like our meta-analysis, Farne et al also observed a modest improvement in quality of life and a small improvement in lung function in both mepolizumab- and reslizumab-treated patients. The clinical outcomes in our study were comparable to the outcomes investigated by Farne et al, except that we included OCS maintenance dose reduction and discontinuation as critical outcomes, because the risk of serious adverse events are substantial with such treatment regimen [36]. Importantly, the study by Farne et al, although largely including the same studies, does not provide an inter-drug comparison of efficacy and safety.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, these effects should be kept in mind while using these drugs. 6,7 Routes of Corticosteroid Administration 1) Local: Adverse effects are less frequent in local treatment than in systemic treatment. a) Topical: Applied over the skin and mucosa.…”
Section: Drugs Used In the Treatment Of Oral Mucosal Diseases 1) Cortmentioning
confidence: 99%
“…Doses should be lowered slowly. 7 The side effects of short-term glucocorticosteroid prescribed for the treatment of mucosal diseases are spontaneously reversible, but those of long-term administration are more serious. Some subjects are at greater risk of the side effects as, for example those with liver disease who do not have the capacity to adequately metabolize the drug, and those with hypoalbuminemia who will have increased levels of free serum glucocorticosteroids.…”
Section: Hydrocortisone Acetatementioning
confidence: 99%
“…The management of both subgroups has been largely based on immunosuppression through corticosteroids and steroid sparing agents, mycophenolate mofetil, azathioprine and cyclophosphamide . Infections, osteoporosis and metabolic derangements are frequently encountered adverse effects secondary to therapy . Numerous advances in our understanding of these diseases have allowed for treatment strategies that go beyond non‐specific immunosuppression .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Infections, osteoporosis and metabolic derangements are frequently encountered adverse effects secondary to therapy. 16,18,[28][29][30][31][32][33] Numerous advances in our understanding of these diseases have allowed for treatment strategies that go beyond non-specific immunosuppression. 34,35 The application of rituximab and intravenous immunoglobulin (IVIg) in combination has shown how different aspects of these diseases can be effectively targeted.…”
Section: Introductionmentioning
confidence: 99%